Remote, but Connected: How #TidyTuesday Provides an Online Community of Practice for Data Scientists - Shrestha, Nischal; Parnin, Chris; Barik, Titus (2021)
Data science practitioners face the challenge of continually honing their skills such as data wrangling and visualization. As data scientists seek online spaces to network, learn and share resources with one another, each individual has to employ their own ad-hoc strategy to practice their data science skills. Given these disjointed efforts, it is crucial to ask: how can we build an inclusive, welcoming online community of practice that unites data scientists in their collective efforts to become experts? Daily hashtags on Twitter are used on specific days and have shown promise in forming a community of practice (CoP) in social networking sites like Twitter, but how do they benefit the community and its members? To understand how daily hashtags benefit data scientists and form an online CoP, we conducted a qualitative study on #TidyTuesday—a daily hashtag project for data scientists using R—using the framework of CoP as a lens for analysis. We conducted semi-structured interviews with 26 participants and uncovered motivations behind their participation in #TidyTuesday, how the project benefited them, and how it cultivated an online CoP. Our findings contribute to the CSCW research on community of practices by providing design trade-offs of using daily hashtags on Twitter, and guidelines on growing and sustaining an online community of practice for data scientists.